TRANSFORMASI PERBANKAN SYARIAH DI INDONESIA (Peluang dan Tantangan Pasca Merger) - Putro Aji, Gatot Bintoro (STMIK Pringsewu, 2025)
The development of Islamic banking in Indonesia is very rapid, most recently three Islamic banks owned by the State-Owned Bank Association (Himbara), namely PT Bank BRI Syariah Tbk (BRIS), PT Bank Syariah Mandiri (BSM), and PT Bank BNI Syariah (BNIS) merged into Bank Syariah Indonesia (BSI). However, the existence of Islamic banks and the merger of the three banks into BSI has not been fully responded to positively by the market. Some Indonesian people, especially Muslims, have not made Islamic banks a reference, in fact they often prefer to use conventional banks. In fact, in its system, BSI refers to sharia principles that guarantee its halalness and are far from usurious systems and practices. This study uses a literature study method. This study concludes that the transformation of BSI has the potential to improve the economy of the Indonesian people. BSI can increase the competitiveness of Islamic finance in the digital era because there are many components that support the creation of superior and trusted Islamic banking. On the other hand, BSI also faces challenges, namely the lack of institutional development, socialization and promotion, quality of human resources and utilization of technology.